PCR assays for detection of Toxoplasma gondii infection in Iranian camels (Camelus dromedarius) of Yazd province - alireza sazmand; mousa tavassoli; bijan Esameilnejad; zahra Asadollahi; ali Kazemnia; seyyedhossein Hekmatimoghaddam (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2014)
The protozoan parasite Toxoplasma gondii is one the most important zoonotic pathogens. Therefore, in the current pilot study a total of 50 Iranian one-humped camels of both sexes and different ages that were kept by local farmers in Yazd province of Iran were tested for Toxoplasma gondii infection. Whole blood samples were investigated by PCR assay using B1 gene. The results revealed that none of the tested camels were infected with Toxoplasma gondii. The current pilot study is the first attempt for detection of Toxoplasma gondii in camels in Iran by PCR method. Further studies in different regions of the country seem necessary to outline the importance of the disease. Also, experimental infection of camels with Toxoplasma gondii is recommended to study the course of the disease.